Sibirian-German - Språkbanken Text (University of Gothenburg, 2024)
The corpus consists of about 34 000 words. Russian words and all verb forms are annotated
(Russian words and hybrids are given in brackets; verb forms have the
attribute FINIT or INFINIT). The SGC has been achieved in cooperation with the Astafyev University in Krasnoyarsk.

Korpusen har c:a 34 000 ord. Ryska ord och alla verbformer har annoterats (ryska ord och hybrider står i
parentes; böjda verbformer får attribut FINIT eller INFINIT). Sibirientyska ingår
i ett samarbetsprojekt mellan Göteborgs universitet och Astafjev universitet
i Krasnojarsk.
Sibirientyska
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik